MOLECULAR AND PHYLOGENETIC STUDY OF THEILERIA SPP ISOLATED FROM TICKS IN AL-DIWANIYAH CITY, IRAQ - & Al-Fatlawi, Al-Fatlawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The current protozoal study was intended to explore the presence and the evolutionary history of Theileria spp in ticks that infecte 150 out of 200 cows in Al-Diwaniyah City, Iraq. For these purposes, 10 ticks were collected from each cow, identified morphologically, and crushed for extract Theileria-based DNA from the tick tissues. The extracted DNA was examined by polymerase chain reaction (PCR) technique for molecularly identificationusing special primer of 18S rRNAgene. The PCR-targeted products of the 18S rRNA gene were subjected to sequencing for further confirmation of the diagnosis of the Theileria spp. The results revealed 2 distinct sequenced protozoa, SP1 and SP2. After performing database searching and comparing the current 2 isolates to some regional and global species, the results showed that the SP1 is closely related to Theileria lestoquardi, KP342263.1 and the SP2 is closely related to Theileria annulata, MF287951.1. The study reveals important information about the evolutionary history of these protozoa in Al-Diwaniyah City, Iraq.